The Application of GPS (Global Positioning System) and SMS Gateway on Hepinar “Helm Pintar” Arduino Microcontroller Based as a Post-Accident Solution - Malikul Fanani; Kukuh Priambodo; Iklil Sulaiman; Sumardi Sumardi (INSIST, 2019)
In Indonesia, the number of death of accident is still pretty high with most of 70% the traffic accident is motorcycle driver who is late in getting aid and the head injury is the first order of all types of experiencing by the accident victim. Prehospital Care is an emergency service when the victim is firstly found, during the process of the transportation until the patient arrives at the hospital Thus, the purpose of this research is the application of GPS (Global Positioning System) and SMS gateway on the safety helmet in order to increase the aid post-accident. The application of GPS has an advantage to receive data from the satellite which next will be stored on arduino microcontroller. Microcontroller will retrieve the driver location data in the forms of latitude, longitude and time. Next, the driver location will be sent by microcontroller via SMS gateway service to the nearest hospital and the victim's family to make the evacuation process easy. This research is tested along the travel of Jember-Lumajang regency. The result of this research is the GPS application on the safety helmet can be applied well. The transmission of driver position coordinate data if the accident happened via sending media of SMS can be applied along with GSM signal from the provider so that the SMS sending works well.